2011
DOI: 10.1186/1472-6963-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Provider performance in treating poor patients - factors influencing prescribing practices in lao PDR: a cross-sectional study

Abstract: BackgroundOut-of-pocket payments make up about 80% of medical care spending at hospitals in Laos, thereby putting poor households at risk of catastrophic health expenditure. Social security schemes in the form of community-based health insurance and health equity funds have been introduced in some parts of the country. Drug and Therapeutics Committees (DTCs) have been established to ensure rational use of drugs and improve quality of care. The objective was to assess the appropriateness and expenditure for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The most common form of informal payments was in cash, which is in line with the findings of previous studies (6,9,10,24,(31)(32)(33). In some studies, most of the informal payments have been made in the form of non-monetary gifts (28,34,35).…”
Section: Discussionsupporting
confidence: 87%
“…The most common form of informal payments was in cash, which is in line with the findings of previous studies (6,9,10,24,(31)(32)(33). In some studies, most of the informal payments have been made in the form of non-monetary gifts (28,34,35).…”
Section: Discussionsupporting
confidence: 87%
“…Annear and Ahmed 2012 ; Alkenbrack et al 2013 ). Further, there is evidence that insured patients had lower expenditure than that of non-insured during hospital stays, although receiving higher quality care ( Syhakhang et al 2011 ; Patcharanarumol et al 2012 ). Studies have also shown that demand-side targeted approaches, such as HEFs, work better than an exemption policy ( Tangcharoensathien et al 2011 ), and that it is more costly to purchase premiums from community health insurance than direct reimbursement from HEFs ( Annear et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The project was unique in its approach through the introduction of health systems research (HSR) in 1998 as part of the institution building and capacity strengthening, in which all authors have been involved in various capacities. All authors also participated from 2005 to 2009 in a research project funded by the European Commission with researchers from 10 institutions in six countries, focusing on poverty and ill-health with the ambition to feed research evidence into health policy in Lao PDR, Cambodia and China through lessons drawn from sub-projects in the three countries ( Bloom et al 2008 ; Meessen et al 2008 ; Ir et al 2010 ; Bloom 2011 ; Syhakhang et al 2011 ). Policymakers at the highest level in the Ministry of Health were consulted during the development of the research project, and the Health Care Law was chosen as a topical case of policy implementation in one of the sub-projects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research question of this study, all sections except section 3 submitted as manuscript elsewhere are included. Variables in the questionnaire were designed after carefully reviewing the past studies from Laos [3436] and elsewhere [3741]. The questionnaire was designed in English, then translated into Laotian and back translated into English to ensure validity.…”
Section: Methodsmentioning
confidence: 99%